Design of Serious Games in the Teaching of Social Responsibility in Higher Education - Rodríguez Carranza, Yemsi Vania (2018)
Management of university social responsibility requires the mainstreaming of contents on sustainable development and social responsibility in the academic field. In this context, this pedagogical experience explores the design of a serious game as a pedagogical tool to obtain an approximate and realistic knowledge of the concepts related to social responsibility, proposing the outline for historicization, referencing, and explaining processes for the design of social responsibility educational games aimed at undergraduate students. Its possible use as a platform for the creative development of students’ sustainable innovation and as a method of evaluating knowledge acquisition of social responsibility is discussed.